2017
DOI: 10.1007/s12544-017-0222-3
|View full text |Cite
|
Sign up to set email alerts
|

Driver behaviour and driver experience of partial and fully automated truck platooning – a simulator study

Abstract: Introduction This paper builds our knowledge of truck driver behaviour in and experience of automated truck platooning, focusing on the effect of partially and fully automated truck platoons on driver workload, trust, acceptance, performance, and sleepiness. Methods Twenty-four male drivers experienced three conditions in a truck driving simulator, i.e., baseline, partial automation, and full automation: the baseline condition was driving with standard cruise control; partial automation was automated longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Part of this reason is that the driver must be able to retake operational control if this is required, for example, due to platoon break-up or complicated road sections. Previous studies have shown that control transition requires a necessary amount of time that varies per driver and per moment (Merat et al 2014), and the level of awareness for the driver is also variable at the moment of control transition (Hjälmdahl, Krupenia, and Thorslund 2017). This poses questions in regard to safety at the point of the transition of control (Axelsson 2017), and also the design of the ADS to allow a driver this time while still maintaining an acceptable level of control.…”
Section: Transition Of Control In Truck Platooningmentioning
confidence: 99%
“…Part of this reason is that the driver must be able to retake operational control if this is required, for example, due to platoon break-up or complicated road sections. Previous studies have shown that control transition requires a necessary amount of time that varies per driver and per moment (Merat et al 2014), and the level of awareness for the driver is also variable at the moment of control transition (Hjälmdahl, Krupenia, and Thorslund 2017). This poses questions in regard to safety at the point of the transition of control (Axelsson 2017), and also the design of the ADS to allow a driver this time while still maintaining an acceptable level of control.…”
Section: Transition Of Control In Truck Platooningmentioning
confidence: 99%
“…If a participant is in high spirits, for example, he/she may feel less sleepy, even after a long distance driving task. Consequently, future studies should systematically focus on how to capture precise data using accurate test techniques, such as through the driving simulator [27]. Third, self-reporting of individual sleepiness level through validated questionnaires may not be accurate due to drivers' faulty memory or incorrect judgment at the time of reporting, at which point they could have a short attention lapse and experience microsleep.…”
Section: Discussion and Practical Implicationsmentioning
confidence: 99%
“…The first is a loss of situation awareness and vigilance, which results from limited vision of the road for drivers in following trucks [10]. The second relates to the platoon lead driver, who now carries responsibility over the entire platoon, and possibly also operational control, which will inadvertently require a high level of trust (in the system and/or themselves) [11]. From a following driver's perspective, it is important to understand the chain of control within a truck platoon.…”
Section: Truck Platooning Control Challengesmentioning
confidence: 99%